Responsabilidade social das empresas: estudo empírico com base nas melhores empresas para trabalhar em Portugal (2017)
The research about the corporate adherence to social responsibility practices has been increasing in recent years. However, there are still few studies seeking to characterize the adherence to social responsibility practices by companies distinguished for being great places to work. In order to reduce this gap, the present research aimed to identify and characterize the social responsibility practices adopted by a group of companies, which integrated three rankings of workplaces in Portugal. For this purpose, we have conducted a descriptive, cross-sectional and quantitative study, based in a questionnaire survey, in order to assess the importance that these companies attribute to the different categories or dimensions that constitute the concept of corporate social responsibility, proposed by Carroll (1979) and Santos et al. (2006), according to their social responsibility practices. The results suggest that companies do not attach equal importance to the various dimensions of corporate social responsibility.